2021
DOI: 10.1055/a-1579-9457
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Findings in Patients with Rare Solitary Necrotic Nodule of the Liver – a Multicenter Report

Abstract: Purpose This multicenter retrospective study highlights the contrast-enhanced ultrasound (CEUS) findings in a series of histologically proven solitary necrotic nodules (SNN) of the liver, a poorly understood pathologic entity of uncertain origin that mimics malignancy. Materials and Methods 22 patients (M/F 13/9; mean age 59.4 years, SD ± 10.7, range 35–81) with histological diagnosis of SNN and CEUS were selected from clinical, imaging, and pathological archives of 7 US interventional centers, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Thus, after injection, contrast shows fast enhancement in tumors, and fast clearance in the advanced arterial phase [20][21][22]. These findings are related to the fact that the abundant blood supply of the hepatic artery and the formation of new blood vessels can accelerate micro-vascular perfusion and blood circulation, thus resulting in a shorter circulation time for contrast agents during the advanced arterial phase [23][24][25]. In this study, we also found that the sensitivity, specificity and accuracy of CEUS for the diagnosis of liver cancer were 91.67%, 95.51% and MVI and the differentiation grade of cancer lesions are important factors that can affect the prognosis and treatment of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after injection, contrast shows fast enhancement in tumors, and fast clearance in the advanced arterial phase [20][21][22]. These findings are related to the fact that the abundant blood supply of the hepatic artery and the formation of new blood vessels can accelerate micro-vascular perfusion and blood circulation, thus resulting in a shorter circulation time for contrast agents during the advanced arterial phase [23][24][25]. In this study, we also found that the sensitivity, specificity and accuracy of CEUS for the diagnosis of liver cancer were 91.67%, 95.51% and MVI and the differentiation grade of cancer lesions are important factors that can affect the prognosis and treatment of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative imaging examination to monitor the lesion is of great importance. SNNL usually presents as heterogeneous hypoechoic nodules on ultrasonography with unclear edges ( 11 ). Enhanced MRI is helpful to distinguish SNNL from other lesions.…”
Section: Discussionmentioning
confidence: 99%
“…has an important influence on the treatment option. Hypoechoic nodules normally appear on abdominal ultrasound of SNNL[ 12 ], hepatic parenchymal tuberculosis[ 13 ], and liver metastatic tumors. Ultrasound has certain limitations in the differential diagnosis of solitary liver nodules.…”
Section: Discussionmentioning
confidence: 99%